2011
DOI: 10.1017/jfm.2011.55
|View full text |Cite
|
Sign up to set email alerts
|

A dynamical instability due to fluid–wall coupling lowers the transition Reynolds number in the flow through a flexible tube

Abstract: A flow-induced instability in a tube with flexible walls is studied experimentally. Tubes of diameter 0.8 and 1.2 mm are cast in polydimethylsiloxane (PDMS) polymer gels, and the catalyst concentration in these gels is varied to obtain shear modulus in the range 17-550 kPa. A pressure drop between the inlet and outlet of the tube is used to drive fluid flow, and the friction factor f is measured as a function of the Reynolds number Re. From these measurements, it is found that the laminar flow becomes unstable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
87
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(103 citation statements)
references
References 35 publications
(44 reference statements)
12
87
4
Order By: Relevance
“…In the experiments of Verma & Kumaran (2012), the transition Reynolds number was found to be lower than theoretical predictions by a factor of 10. Moreover the scaling of the transition Reynolds number was found to be Re ∝ 5/8 , in between those for the inviscid and wall modes.…”
Section: High Reynolds Numbermentioning
confidence: 63%
See 2 more Smart Citations
“…In the experiments of Verma & Kumaran (2012), the transition Reynolds number was found to be lower than theoretical predictions by a factor of 10. Moreover the scaling of the transition Reynolds number was found to be Re ∝ 5/8 , in between those for the inviscid and wall modes.…”
Section: High Reynolds Numbermentioning
confidence: 63%
“…Due to this, it was considered infeasible to practically realise the high Reynolds number instability at a Reynolds number lower than that for transition in a rigid tube/channel. Due to this, the results of Verma & Kumaran (2012) for the flow through a soft tube, and Verma & Kumaran (2013) for a channel flow discussed a little later, were surprising.…”
Section: High Reynolds Numbermentioning
confidence: 98%
See 1 more Smart Citation
“…The predictions for low Re seem to be quite sensitive to the nature of the constitutive models used, while at high Re, predictions are relatively insensitive to the models. Experimental observations (Verma & Kumaran 2012 in deformable circular tubes and rectangular channels do show instabilities at Re ∼ 500, but they also show that there is a change in the tube cross-section due to applied pressure gradient. If this change is accounted for, then there is reasonably good agreement between the wall mode predictions and experimental observations, as argued by Verma & Kumaran (2013).…”
Section: Discussionmentioning
confidence: 91%
“…Later, Chokshi (2007) carried out a weakly nonlinear analysis for wall modes as well, and showed that the instability is always supercritical at higher Re. Although experimental studies in flow through deformable tubes exhibit an instability (Verma & Kumaran 2012), it is not yet clear whether there is evidence on the nature of the bifurcation.…”
Section: Weakly Nonlinear Stabilitymentioning
confidence: 99%